Prevalence of β-cell antibodies and associated autoimmune diseases in children and adolescents with type 1 diabetes (T1DM) versus type 2 diabetes (T2DM) in Qatar - Alyafei, Fawzia; Soliman, Ashraf; Alkhalaf, Fawziya; Sabt, Aml; De Sanctis, Vincenzo; Elsayed, Nagwa; Waseef, Reem (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Type 1 diabetes mellitus (T1DM) is an autoimmune disease with the development of abnormal immune responses to specific β-cell autoantigens in addition to other organ-specific autoimmunity. The most frequent associated disorders are thyroid dysfunctions and celiac disease. There are limited studies in the current literature on the prevalence of associated autoimmunity, especially multiple, in children and adolescents with T1DM and Type 2 diabetes mellitus (T2DM). Objectives: The aim of the present study was to determine the prevalence of autoantibodies and thyroid dysfunctions in a cohort of children and adolescents (aged 0.5-16 years) with T1DM living in Qatar. Research design and methods: The records of all children and adolescents attending the Pediatric Diabetes Center of Hamad Medical Center, for the past 5 years (from January 2012 to December 2016), were reviewed and all clinical and biochemical data, including β-cell autoimmunity [anti-glutamic acid decarboxylase (GAD) antibodies, anti-islet cell and anti-insulin antibodies (IAA)], thyroid function (Free thyroxine: FT4 and thyroid-stimulating hormone: TSH), anti-thyroid peroxidase antibodies (TPO) and anti-tissue transglutaminase (ATT) were collected at their first presentation (cross-sectional study). Data for patients with T1DM (n=431) and T2DM (n=59) were recorded analyzed and the prevalence calculated and compared with other studies. Results: The prevalence of anti-GAD antibodies was 75.5 % in T1DM and 29.3% in T2DM. Anti β-islet antibodies (Ab) were detected in 53.4% of T1DM and 29.4% of T2DM. Anti-insulin Ab were detected in 40.4% of T1DM and 58.3% of T2DM. The three antibodies together were detected in 18.4 % of T1DM and none of T2DM. At presentation, hypothyroidism (FT4